Orthognathic surgery in the treatment of obstructive sleep apnea syndrome - Michele García Menéndez; Pedro Antonio Ducasse Olivera; Yusleni Hernández Gálvez; Jeydel Abull Jauregui; Olga Ileana Ruiz Galvez; Elena Cuspineda Bravo (Editorial Ciencias Médicas, 2020)
Introduction: Obstructive sleep apnea syndrome causes daytime sleepiness, affects the cardiovascular system and reduces the quality of life. Since orthognathic surgery brings about changes in the pharyngeal airway space, it has been used to treat this syndrome. Objective: Characterize the orthognathic surgery techniques most commonly used to treat obstructive sleep apnea syndrome, their impact on the pharyngeal airway and their therapeutic effectiveness. Methods: A bibliographic review was conducted from December 2016 to June 2017 using the search engines and platforms SciELO, Medline, Pubmed and Hinari. The search words used were orthognathic surgery, obstructive sleep apnea syndrome, pharyngeal airway, maxillomandibular advancement, and combinations thereof. Of the 127 papers obtained, 28 were selected based on their content, topicality and objectivity. Data analysis and integration: Surgical advancement of the maxilla, mandible, chin or combinations thereof minimizes the effects of obstructive sleep apnea syndrome. Bimaxillary surgery is recommended to correct skeletal class III malocclusion so as to lessen potential damaging effects on the airway caused by isolated mandibular retroposition. Conclusions: Advancement orthognathic surgery broadens the pharyngeal airway space and improves the quality of sleep. The fact that retroposition movements may have an opposite effect is an important aspect to be considered in the correction of skeletal class III malocclusions.